2007
DOI: 10.1016/j.brainres.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Regional dissection and determination of loosely bound and non-heme iron in the developing mouse brain

Abstract: Iron is a trace metal essential for normal brain development but toxic in excess as it is capable of generating highly reactive radicals that damage cells and tissue. Iron is stringently regulated by the iron regulatory proteins, IRP1 and IRP2, which regulate proteins involved in iron homeostasis at the posttranscriptional level. In this study, 12 distinct regions were microdissected from the mouse brain and regional changes in the levels of loosely bound and non-heme iron that occur with development were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Magaki et al . 55 measured “loosely bound iron” and “non-heme iron”, defined operationally, in 6, 12, and 24 week old mouse brains. They found that loosely bound Fe represented 20% – 30% of non-heme Fe, with the latter type of Fe increasing with age and the former decreasing slightly or remaining constant.…”
Section: Discussionmentioning
confidence: 99%
“…Magaki et al . 55 measured “loosely bound iron” and “non-heme iron”, defined operationally, in 6, 12, and 24 week old mouse brains. They found that loosely bound Fe represented 20% – 30% of non-heme Fe, with the latter type of Fe increasing with age and the former decreasing slightly or remaining constant.…”
Section: Discussionmentioning
confidence: 99%
“…More than three-fold increases of ferritin were directly observed in the 3D distribution of ferritin by electron tomography in different regions of brains of Irp1 +/− Irp2 −/− mice, and structural damage was observed within the axons (Zhang et al, 2005). The Kirsch group found that both loosely bound iron and non-heme iron increased during development between 6 and 12 weeks of age in Irp2 −/− mice, whereas the reverse was observed for WT mice (Magaki et al, 2007). …”
Section: The First Irp2 Knockout Mouse Modelmentioning
confidence: 99%
“…Aberrant brain metal levels have been associated with normal aging and a variety of diseases however this is still debated [19, 258]. …”
Section: Putative Causes and Risk Factors Involved In Pdmentioning
confidence: 99%